Sengketa Perbuatan Melawan Hukum dalam Sistem Civil Law, Common Law, dan Hukum Islam - Shihaf Ismi Salman Najib (Jurist-Diction, 2024)
Abstract Wrongful Acts of Law (PMH) is a common issue, but it is still often ignored in a cross-border context. This research aims to enrich the discussion on the importance of PMH rules in international civil law by using normative research methods. PMH in the Continental European, Anglo-American, and Islamic law systems refers to actions that harm other parties and give rise to the victim's right to compensation and the perpetrator's obligation to pay compensation. In the context of international civil law, there are three important principles: lex loci delicti commissi (the law of the place where the act was committed), lex fori (the law of the court handling the case), and the proper law of tort (the law most relevant to the dispute). These principles are used to determine the quality and application of the law relating to cross-border PMH. Abstrak Perbuatan Melawan Hukum (PMH) merupakan isu umum, namun dalam konteks lintas negara masih sering diabaikan. Penelitian ini bertujuan memperkaya pembahasan mengenai pentingnya aturan PMH dalam hukum perdata internasional dengan menggunakan metode penelitian normatif. PMH dalam sistem hukum Eropa Kontinental, Anglo-American, dan Islamic law mengacu pada perbuatan yang merugikan pihak lain dan menimbulkan hak korban untuk mendapat ganti rugi serta kewajiban pelaku untuk membayar kompensasi. Dalam konteks hukum perdata internasional, terdapat tiga asas penting: lex loci delicti commissi (hukum tempat perbuatan dilakukan), lex fori (hukum pengadilan yang menangani perkara), dan the proper law of tort (hukum yang paling relevan dengan sengketa). Asas-asas ini digunakan untuk menentukan kualitas dan penerapan hukum terkait PMH lintas negara.